Text-fig. 6. a: cf. Rubus sp., leaflet Oriolo MSF 676. b, c: cf. Sorbus. b: Oriolo MSF 821. c: MSF 677. d: Spiraea aff. cana Oriolo MSF 944. e: Rhamnus aff. cathartica Oriolo MSF 909. f–l: Ulmus affinis. f: Oriolo MSF 717. g: Oriolo MSF 725. h: Oriolo MSF 724. i: Oriolo MSF 721. j: Oriolo MSF 723. k: Oriolo MSF 637. l: Oriolo MSF 722. m: Zelkova zelkovifolia Oriolo 28 MSF 633. Scale bars 10 mm (a–f, m), 50 mm (g–l). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 6. a: cf. Rubus sp., leaflet Oriolo MSF 676. b, c: cf. Sorbus. b: Oriolo MSF 821. c: MSF 677. d: Spiraea aff. cana Oriolo MSF 944. e: Rhamnus aff. cathartica Oriolo MSF 909. f–l: Ulmus affinis. f: Oriolo MSF 717. g: Oriolo MSF 725. h: Oriolo MSF 724. i: Oriolo MSF 721. j: Oriolo MSF 723. k: Oriolo MSF 637. l: Oriolo MSF 722. m: Zelkova zelkovifolia Oriolo 28 MSF 633. Scale bars 10 mm (a–f, m), 50 mm (g–l). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 229, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867